Factors Related To Family Planning After Birth In The Working Way Of Dadok Tunggul Hitam Public Health Centre In 2023: Factors Related To Family Planning After Birth - Devi Syarief; Yulia Arifin; Riri Defriani (International Journal of Midwifery and Health Sciences, 2024)
Indonesia is the fourth most populous country in the world with a population of 273,879,750. To overcome population problems and reduce TFR (Total Fertility Rate) with contraceptive services and spacing of pregnancies through post-coital family planning. One of the behavioral determinants associated with the use of post-saline family planning includes maternal knowledge, attitudes and husband support. The purpose of this study was to determine the factors associated with the use of postpartum family planning in the working area of Dadok Tunggul Hitam Public Health Centre Padang City. This study is an analytic study with a cross sectional study approach with a sample size of 49 postpartum mothers using total sampling. Data analysis used univariate and bivariate with Chi-Square test. The results of the bivariate analysis showed that there was a relationship between the number of children, (p-value 0.006), knowledge (p-value 0.002), attitudes (p-value 0.007), and husband support (p-value 0.001) to the use of postpartum family planning.